Electrochemical generation of microbubbles by carbon nanotube interdigital electrodes to increase the permeability and material uptakes of cancer cells. (1st January 2019) - Khayamian, Mohammad Ali; Shalileh, Shahriar; Vanaei, Shohreh; Salemizadeh Parizi, Mohammad; Ansaryan, Saeid; Saghafi, Mohammad; Abbasvandi, Fereshteh; Ebadi, Amirali; Soltan Khamsi, Pouya; Abdolahad, Mohammad
Abstract: Artificial cavitation as a prerequisite of sonoporation, plays an important role on the ultrasound (US) assisted drug delivery systems. In this study, we have proposed a new method of microbubble (MB) generation by local electrolysis of the medium. An integrated interdigital array of three-electrode system was designed and patterned on a nickel-coated quartz substrate and then, a short DC electrical pulse was applied that consequently resulted in distributed generation of microbubbles at the periphery of the electrodes. Growth of the carbon nanotube (CNT) nanostructures on the surface of the electrodes approximately increased the number of generated microbubbles up to 7-fold and decreased their average size from ∼20 µm for bare to ∼7 µm for CNT electrodes. After optimizing the three-electrode system, biocompatibility assays of the CNT electrodes stimulated by DC electrical micropulses were conducted. Finally, the effect of the proposed method on the sonoporation efficiency and drug uptake of breast cells were assessed using cell cycle and Annexin V/PI flow cytometry analysis. These results show the potential of electrochemical generation of MBs by CNT electrodes as an easy, available and promising technique for artificial cavitation and ultrasound assisted drug delivery.